PENGEMBANGAN INSTRUMEN DETERMINASI DIRI SISWA DALAM PEMBELAJARAN MATEMATIKA - Nurul Fadilah Annisa; Kadir Kadir; Ahmad Dimyati (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2022)
The purpose of this research is to develop students' self-determination instruments in learning mathematics. This research is development research with the stages of of define, design, and develop. The research was conducted at a high school in South Tangerang in the 2021/2022 Academic Year involving 368 class XI students as respondents. Data analysis techniques use theoretical validation and empirical validation. Theoretical validation was through expert panelist assessment using the Aiken's V method, while empirical validation was using confirmatory factor analysis techniques. The results of the study revealed: (1) Theoretical validation, obtained 20 valid items with Aiken's V (0.75 - 1.00), p-value <0.05. Empirical validation, obtained 13 out of 20 items declared valid (t-count> 1.96). Reliability is classified as good with Cronbach's Alpha of 0.685, with construct reliability (CR) indicators of autonomy (CR = 0.330), competence (CR = 0.247), and relatedness (CR = 0.714). The self-determination construct model fits the empirical data, with an instrument readability percentage of 95% or very good. (2) Overall self-determination of students in learning mathematics is in the high category (76.23%), consisting of 71.78% autonomous indicators, 73.56% competence, and 81.58% relatedness. There are differences in students' self-determination in learning mathematics in terms of gender, school, major, origin of junior high school, and mother's level of education. The conclusion of this study is that the indicators of autonomy, competence, and relatedness are valid and consistent in measuring students' self-determination in learning mathematics.Tujuan penelitian ini adalah mengembangkan instrumen determinasi diri siswa dalam pembelajaran matematika. Penelitian ini adalah penelitian pengembangan dengan tahapan pendefinisian, perancangan, dan pengembangan. Penelitian dilakukan di suatu sekolah menengah atas di Tangerang Selatan pada Tahun Ajaran 2021/2022 dengan melibatkan 368 siswa kelas XI sebagai responden. Teknik analisis data menggunakan validasi teoretis dan validasi empiris. Validasi teoretis melalui penilaian panelis ahli dengan metode Aiken’s V, sedangkan validasi empiris menggunakan teknik analisis faktor konfirmatori. Hasil penelitian mengungkapkan: (1) Validasi teoretis, diperoleh 20 butir valid dengan Aiken’s V (0,75 – 1,00), p-value < 0,05. Validasi empiris, diperoleh 13 butir dari 20 butir dinyatakan valid (t-hitung > 1,96). Reliabilitas tergolong baik dengan Cronbach's Alpha sebesar 0,685, dengan construct reliabilty (CR) indikator otonomi (CR = 0,330), kompetensi (CR = 0,247), dan keterkaitan (CR = 0,714). Model konstruk determinasi diri cocok (fit) dengan data empiris, dengan persentase keterbacaan instrumen sebesar 95% atau sangat baik. (2) Secara keseluruhan determinasi diri siswa dalam pembelajaran matematika berada dalam kategori tinggi (76,23%), terdiri dari indikator otonom 71,78%, kompetensi 73,56%, dan keterkaitan 81,58%. Terdapat perbedaan determinasi diri siswa dalam pembelajaran matematika ditinjau dari jenis kelamin, sekolah, jurusan, asal SLTP, dan tingkat pendidikan Ibu. Simpulan penelitian ini adalah bahwa indikator otonomi, kompetensi, dan keterkaitan valid dan konsisten mengukur determinasi diri siswa dalam pembelajaran matematika.